Impact of intratumoural CD96 expression on clinical outcome and therapeutic benefit in gastric cancer. Issue 12 (3rd October 2022) - Xu, Chang; Fang, Hanji; Gu, Yun; Yu, Kuan; Wang, Jieti; Lin, Chao; Zhang, Heng; Li, He; He, Hongyong; Liu, Hao; Li, Ruochen
Abstract: CD96 was identified as a novel immune checkpoint. However, the role of CD96 in the gastric cancer (GC) microenvironment remains fragmentary. This study aimed to probe the clinical significance of CD96 to predict prognosis and therapeutic responsiveness, and to reveal the immune contexture and genomic features correlated to CD96 in GC patients. We enrolled 496 tumor microarray specimens of GC patients from Zhongshan Hospital (ZSHS) for immunohistochemical analyses. Four hundred and twelve GC patients from the Cancer Genome Atlas (TCGA) and 61 GC patients treated with pembrolizumab from ERP107734 published in the European Nucleotide Archive (ENA) were gathered for further analysis of the association between CD96 + cell infiltration and immune contexture, molecular characteristics, and genomic features by CIBERSORT and gene set enrichment analysis. Clinical outcomes were analyzed by Kaplan–Meier curves, the Cox model, interaction testing, and receiver operating characteristic analysis. High CD96 + cell infiltration predicted poor prognosis and inferior survival benefits from fluorouracil‐based adjuvant chemotherapy in the ZSHS cohort whereas superior therapeutic responsiveness to pembrolizumab was shown in the ENA cohort. CD96‐enriched tumors showed an immunosuppressive tumor microenvironment featured by exhausted CD8 + T‐cell infiltration in both the ZSHS and TCGA cohorts. Moreover, in silico analysis for the TCGA cohort revealed that several biomarker‐targeted pathways displayed significantly elevated enrichment levels in the CD96 high subgroup. This study elucidated that CD96 might drive an immunosuppressive contexture with CD8 + T‐cell exhaustion and represent an independent adverse prognosticator in GC. CD96 could potentially be a novel biomarker for precision medicine of adjuvant chemotherapy, immunotherapy, and targeted therapies in GC. Abstract : CD96 + cells infiltration represented an independent adverse prognosticator and could predict prognosis of adjuvant chemotherapy and therapeutic responsiveness to PD‐1 inhibitor. Immunosuppression by CD96 level was characterized by exhausted CD8 + T cells.